2001
DOI: 10.1002/app.1818
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and glass transition temperature of poly(styrene‐b‐butyl methacrylate) block copolymers by stable free radical polymerization

Abstract: ABSTRACT:The synthesis of controlled polystyrenes with different molecular weights has been performed in the presence of 1-phenyl-1-(2,2,6,6-tetramethyl-1-piperidinyloxy)ethane (PETEMPO). The polystyrenes have served as macroinitiators for the formation of poly(styrene-b-butyl methacrylate) block copolymers. Using differential scanning calorimetry (DSC) it has been shown that all block copolymers synthesized do not present phase segregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…In these cases, two glass transitions were detected by DSC, which confirmed that phase separation had taken place. This effect of the increase in the macroinitiator concentration is in accordance with earlier findings by Fernandez‐Garcia et al40 from studies on poly( tert ‐butyl acrylate‐ g ‐styrene) copolymers. The higher macroinitiator concentration shifted the weak crystallization peaks ( T c ) toward much lower temperatures (from +2 to −12 °C) in comparison with T c of the synthesized copolymer (M/I = 300) and T c of the corresponding homopolymer in the bulk state.…”
Section: Resultssupporting
confidence: 92%
“…In these cases, two glass transitions were detected by DSC, which confirmed that phase separation had taken place. This effect of the increase in the macroinitiator concentration is in accordance with earlier findings by Fernandez‐Garcia et al40 from studies on poly( tert ‐butyl acrylate‐ g ‐styrene) copolymers. The higher macroinitiator concentration shifted the weak crystallization peaks ( T c ) toward much lower temperatures (from +2 to −12 °C) in comparison with T c of the synthesized copolymer (M/I = 300) and T c of the corresponding homopolymer in the bulk state.…”
Section: Resultssupporting
confidence: 92%